High-growth firm shares in Austrian regions: The role of economic structures - Klaus S. Friesenbichler; Werner Hölzl (Austrian Institute of Economic Research (WIFO), 2020)
This paper explores the structural determinants of high-growth firm shares in Austrian regions. The regional level of analysis allows to uncover regularities which are not detectable in firm-level studies. We find that lower mobility barriers, firm exits and technological opportunities, measured by digitalisation intensities, and, to a lesser extent, agglomeration effects are associated with a larger share of high-growth firms. The results suggest that comparisons of shares of high-growth firms across countries and regions should consider differences in the industrial structures together with the often-emphasised differences in policies and regulations.
Keywords: D22; L25; R11; 330; high growth firms; industrial structure; ICT; Austria; variety; NUTS-3